2011
DOI: 10.1371/journal.pone.0023167
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Proline-Rich Tandem Repeat Proteins Reveals Broad Phylogenetic Diversity in Plant Secretomes

Abstract: Cell walls, constructed by precisely choreographed changes in the plant secretome, play critical roles in plant cell physiology and development. Along with structural polysaccharides, secreted proline-rich Tandem Repeat Proteins (TRPs) are important for cell wall function, yet the evolutionary diversity of these structural TRPs remains virtually unexplored. Using a systems-level computational approach to analyze taxonomically diverse plant sequence data, we identified 31 distinct Pro-rich TRP classes targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…The viscoelastic properties of mucus, slimes, and other viscous biofluids are determined in large part by the formation of extended and entangled structures by mucins such as the SCPP mucin 7 (Supplementary Table S4, http:// dx.doi.org/10.3168/jds.2013-6831; Schenkels et al, 1995;Thornton et al, 2008;Senapati et al, 2010). Likewise, P,Q-rich proteins readily form gels; for example, the seed storage prolamins wheat gliadin and barley hordein (Shewry and Halford, 2002) or the plant cell wall extensins (Newman and Cooper, 2011). Extended hydrated structures and low sequence specificity both point to a predominance of main-chain interactions mediated by direct H-bonding or through bridging water molecules.…”
Section: Quaternary Structures and The Hydrophobic Effectmentioning
confidence: 99%
“…The viscoelastic properties of mucus, slimes, and other viscous biofluids are determined in large part by the formation of extended and entangled structures by mucins such as the SCPP mucin 7 (Supplementary Table S4, http:// dx.doi.org/10.3168/jds.2013-6831; Schenkels et al, 1995;Thornton et al, 2008;Senapati et al, 2010). Likewise, P,Q-rich proteins readily form gels; for example, the seed storage prolamins wheat gliadin and barley hordein (Shewry and Halford, 2002) or the plant cell wall extensins (Newman and Cooper, 2011). Extended hydrated structures and low sequence specificity both point to a predominance of main-chain interactions mediated by direct H-bonding or through bridging water molecules.…”
Section: Quaternary Structures and The Hydrophobic Effectmentioning
confidence: 99%
“…Showalter et al [2 and unpublished data] conducted the identification of the HRGP superfamily in Arabidopsis thaliana and Populus trichocarpa in which 59 and 60 EXTs were identified, respectively. In addition, Newman and Cooper [ 27 ] identified numerous proline-rich tandem repeat proteins (TRPs) including EXTs through a bioinformatics approach using EST and NCBI Non-Redundant protein sequence data of a number of plant species, but the search criteria for TRPs were not tailored for identifying EXTs. Nonetheless, knowledge about the number and distribution of EXTs in plant kingdom is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Another, less biased approach based on a clustering method was used by Newman and Cooper (2011) to search for tandem repeats to identify Pro-rich proteins in plants. While EXTs were able to be identified, this method was poor in detecting AGPs because their diagnostic AP, SP, and TP glycomotifs that direct arabino-3,6-galactan-type glycosylation (Tan et al, 2003) are scattered throughout the protein backbone, rather than being found in tandem (Schultz et al, 2002;Showalter et al, 2010).…”
mentioning
confidence: 99%